2013
DOI: 10.1158/1055-9965.epi-12-0860
|View full text |Cite
|
Sign up to set email alerts
|

Age-Dependent Associations between Androgenetic Alopecia and Prostate Cancer Risk

Abstract: Background: Both prostate cancer and androgenetic alopecia are strongly age-related conditions that are considered to be androgen dependent, but studies of the relationship between them have yielded inconsistent results. We aimed to assess whether androgenetic alopecia at ages 20 and 40 years are associated with risk of prostate cancer.Methods: At a follow-up of the Melbourne Collaborative Cohort Study, men were asked to assess their hair pattern at ages 20 and 40 years relative to eight categories in showcard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 23 publications
0
24
1
Order By: Relevance
“…Age-adjusted prostate cancer risk (PCa) and mortality by self-reported vitamin use among 11,795 men participating in the third screening round of the Finnish Prostate Cancer Screening Trial. 9448 men, male pattern baldness at the age of 40 was associated with an increased risk of PCa, but later male type baldness at the age of 70 and over had a protective effect, and the cumulative probability for PCa between the groups converged at the age of 76 years [11]. This suggests that male pattern baldness at a certain age could be connected with earlier onset of PCa.…”
Section: Discussionmentioning
confidence: 95%
“…Age-adjusted prostate cancer risk (PCa) and mortality by self-reported vitamin use among 11,795 men participating in the third screening round of the Finnish Prostate Cancer Screening Trial. 9448 men, male pattern baldness at the age of 40 was associated with an increased risk of PCa, but later male type baldness at the age of 70 and over had a protective effect, and the cumulative probability for PCa between the groups converged at the age of 76 years [11]. This suggests that male pattern baldness at a certain age could be connected with earlier onset of PCa.…”
Section: Discussionmentioning
confidence: 95%
“…However, the median of baseline age was about 55 years, when baldness was assessed, and therefore baldness at younger age was not evaluated with sufficient statistical power. The Melbourne Collaborative Cohort Study (MCCS) predicted an 81% increased risk for prostate cancer at age 55 years, comparing vertex balding (Norwood-Hamilton stage III vertex –VII) with no balding at age 40 years [36]. This study also suggested that vertex balding at 40 years was associated with an average three-year earlier age at prostate cancer diagnosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…The Melbourne Collaborative Cohort Study (MCCS) predicted an 81% increased risk for prostate cancer at age 55 years, comparing vertex balding (Norwood-Hamilton stage III vertex –VII) with no balding at age 40 years [36]. This study also suggested that vertex balding at 40 years was associated with an average three-year earlier age at prostate cancer diagnosis [36]. However, male pattern baldness was self-assessed after prostate cancer diagnosis, and men with aggressive prostate cancer were more likely to dropout from follow-up resulting in differentially missing self-reported hair-loss patterns.…”
Section: Discussionmentioning
confidence: 99%
“…(1214) Although most studies show some variability in prevalence depending on age, ethnic composition of the sample and study design (population-based vs. hospital-based and reference age for baldness), our results are similar to several other studies that support an increased prevalence of early onset baldness among prostate cancer cases and an association of baldness with early onset prostate cancer. (10, 16, 26) Unfortunately, the prevalence of early pattern baldness types among African-American prostate cancer cases and controls has not been documented.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to their findings, a recent large prospective study of 9,448 Australian men found that baldness at age 40 rather than age 20 was predictive of early onset prostate cancer. (26) It has been suggested that age 20 may be too early to observe associations of baldness on prostate cancer, as many men that will experience early onset baldness have not yet begun balding by that age. An age range between 30–40 seems more appropriate as a reference point to avoid misclassification of early pattern baldness and is also a closer timepoint to prostate cancer diagnosis and related processes.…”
Section: Discussionmentioning
confidence: 99%